#EndMaleGuardianship: Women's rights, social media and the Arab public sphere. (May 2019) - Thorsen, Einar; Sreedharan, Chindu
This study examines the online communicative dynamics between women and men during the Saudi women's rights campaign to end male guardianship, which unfolded on Twitter. We analysed 2.7 million tweets with the #EndMaleGuardianship hashtag over a 7-month period quantitatively and 150, 245 of these qualitatively to examine the extent to which Twitter shapes and facilitates cross-gender communication, and how this helped engender new spaces for expression of dissent. Our study shows that Twitter provided shared online communicative spaces that had several characteristics commonly associated with public sphere(s). There is also evidence that using these alternatives spaces, women transcended to an extent the gender segregation that exists in traditional public discourses and spaces of Saudi society. The anonymity of Twitter offered women a safe place to deliberate their concerns about male guardianship. We suggest that these deliberations created a counterpublic sphere of sorts, which helped Saudi women legitimise the #EndMaleGuardianship campaign.